Arterial complications after laparoscopic cholecystectomy: single centre experience - A., Arunkumar; Urabinahatti, Kiran; Rajendran, Kamalakannan; Thangasamy, Selvaraj; Sathyanesan, Jeswanth (International Surgery Journal, 2023)
Laparoscopic cholecystectomy is one of the most common surgeries done in general surgical practice. Arterial complications after laparoscopic cholecystectomy are not uncommon and usually results due to iatrogenic injury. Mostly patients are managed by interventional radiological procedures, but very rarely we may have to resort to surgical procedures also. Our first patient a 40-year-old female patient presented with haemetemesis and malena. She was diagnosed with a right hepatic artery aneurysm following a laparoscopic cholecystectomy done 2 months back. Due to sudden haemodynamic instability, the patient underwent laparotomy aneurysmal excision and T tube drainage. Later T tube was removed. Another patient, a 41-year-old female patient presented to us with haemetemesis and malena 2 weeks after laparoscopic cholecystectomy. She developed a post-operative biliary leak and was managed with USG-guided pigtail drainage. She was later diagnosed with a GDA aneurysm along with mid-CBD transection. The patient was later managed with hepatico jejunostomy. Our third patient is a 52-year-old gentleman, underwent interval laparoscopic cholecystectomy following acute calculus cholecystitis. Intra operatively following profuse bleeding, RHA artery sectoral branch repair was done. Patient continued to have bleeding and he underwent emergency angioembolisation of right hepatic artery pseudo aneurysm. Arterial complications following laparoscopic cholecystectomy result either from direct arterial or combined Bilio arterial injuries. Interventional radiological procedures are still considered the standard of care in these situations. Surgical interventions hold equally good in ongoing bile leak and in failure of embolization techniques. Management strategy depends on the clinical profile of the patient and the injuries associated with it.